Nutrition and enhanced sports performance : muscle building, endurance, and strength - Bagchi, Debasis, 1954-; Nair, Sreejayan; Sen, Chandan K. (Elsevier AP, 2013)
"Nutrition and Enhanced Sports Performance: Muscle Building, Endurance, and Strength provides a comprehensive overview to understanding the integrated impact of nutrition on performance. The book is divided into five main themes: An introductory overview of the role of nutrition in human healthVarious types of physical exercises, including cardiovascular training, resistance training, aerobic and anaerobic exercise, bioenergetics, and energy balance. This section also covers the nutritional requirements associated with various fitness programs, as well as exercis."-- Resumé vydavatele
Keywords: výživa člověka; sport; sportovci; sportovní výkony; svaly; human nutrition; sportsmen; sports performance; muscles; kolektivní monografie; elektronické knihy; collective monographs; electronic books